Apple snail perivitellins, multifunctional egg proteins - Heras, Horacio (2017)
Egg reserves of most gastropods are accumulated surrounding the fertilised oocyte as a perivitelline fluid (PVF). Its proteins, named perivitellins, play a central role in reproduction and development, though there is little information on their structural-functional features. Studies of mollusc perivitellins are limited to Pomacea. A proteomic study of the eggs of P. canaliculata identified over 59 proteins in the PVF, most of which are of unknown function, and have not been isolated and characterised. Information on molecular structure of the most abundant perivitellins of P. canaliculata have shown that they possess other functions besides being storage proteins, most remarkably in defence against predation and abiotic factors. They are a cocktail containing at least neurotoxic, antinutritive and antidigestive perivitellins, with others that may provide the eggs with a bright and conspicuous colour (aposematic signal). This review compiles the current knowledge of Pomacea perivitellins with emphasis on the novel physiological roles they play in the reproductive biology of these gastropods that have evolved the ability to lay their eggs above the water.